HAK KONSTITUSIONAL PEGAWAI NEGERI SIPIL (PNS) DALAM PENCALONAN SEBAGAI KEPALA DAERAH - Inong, Inong (Katalogis, 2015)
Public servant issues concern with designation, task, duties, rights and development of public servants. Among quite number public servant issues, the ones on the rights and obligations of public servants, including their rights to nominate themselves for a post of Regent/ Mayor/ Governor, will be elaborated. In Indonesia, the essence of rights of an Indonesian citizen are provided in Article 27 Section (1) and Article 28D Section (3) of the Indonesian Constitution Year 1945 concerning with the rights of Indonesian citizens and universal principles of freedom. Article 123 Section (3) of Law Namber 5 Year 2014 about Civil Apparatus provides about Nomination to be Regent/Mayor/Governor, requiring a written resignation as of the date of nomination. Accordingly, there is potentially a conflict with the Article 27 and Article 28D of the Indonesian Constitution Year 1945, providing about the intention of ‘each Indonesian citizen’. In order to study the issue, this research adopted juridical and normative approaches. They were both adopted as the researcher focused on laws and regulations, legal principles, doctrines or concepts related with reviews to the composition of rights of public servants qualitatively analyzed based on the laws. Normatively, Article 123 Section (3) of Law Number 5 Year 2014 about Public Servant provides that despite his duties to serve the people, any public servant nominating himself for a post as Regent/ Mayor/ Governor shall first resign from being a public servant and remain neutral and professional. Being neutral is supposed not to use any state facilities, to be proportional and accountable in delivering services to the people.